Detoxification of Azo Dyes Mediated by Cell-Free Supernatant Culture with Manganese-Dependent Peroxidase Activity: Effect of Mn 2+ Concentration and H 2o 2 Dose - Contreras-Villacura, E; Urra-Hernandez, J; Vasquez-Perez, O (2012)
White-rot fungi (WRF) are capable of degrading complex organic compounds such as lignin, and the enzymes that enable these processes can be used for the detoxification of recalcitrant organopollutants. The aim of this study is to evaluate a system based on the use of an in vitro ligninolytic enzyme for the detoxification of recalcitrant dye pollutants. The dyes selected for investigation were the anionic and cationic commercial azo dyes, basic blue 41 (BB41), acid black 1 (AB1), and reactive black 5 (RB5). A supernatant, cell-free culture of WRF with manganese peroxidase activity was used to investigate its degradative capacity under various conditions, and concentrations of cofactors, H 2O 2 and Mn 2+. The assays were carried out using a 2 2 experimental designs whose variables were concentration of Mn 2+ (33 and 1,000 ?M) and semicontinuous dosage of the H 2O 2 (0.02 and 0.10 ?mol) added at a frequency of 0.2 min -1. The response variables analyzed were the efficiency and the initial rate of the decolorization process. The dye concentrations considered ranged from 10 to 200 mg L -1. AB1 and RB5 were decolorized over the entire interval of concentrations studied; reaching efficiencies between 15 and 95%. Decolorization of up to 100 mg L -1, BB41 had less than 30% efficiency. The decay of the concentration of AB1 was interpreted by two-stage kinetics model, with the exception of the condition of 33 ?M Mn 2+-0.02 ?mol of H 2O 2 in which only one stage was observed. For all assays performed with 33 ?M Mn 2+, the initial rate of the decolorization process was found to be dependent on the dosage of H 2O 2. The results of this study can be applied to the development bioreactors for the degradation of recalcitrant pollutants from the textile industry and may be used as a model for expanding the use of extracellular enzyme supernatants in bioremediation. © 2011 American Institute of Chemical Engineers (AIChE).
Keywords: degradation or decolorization; in vitro; dyes